1991
DOI: 10.1111/j.1477-9552.1991.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Discount Rate for Land‐use Projects in India

Abstract: The social discount rate is derived from an inter-temporal social utility model or land-use projects in India. The social discount rate is a function o f two parameters: the elasticity of social marginal utility of consumption and the growth rate of per capita real consum tion. The final results for the social discount rate and the elasticity o{ocial marginal utility of consum tion are 2 per cent and -1.4 respectively. found in the literature. These values are plausib f e and comparable with other estimatesSoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…From the plausible and statistically valid income and compensated price elasticity estimates of the demand for food, an estimated e value of ¡ 1:60 was derived (see previous section for full details on this). In fact, further estimation of this same demand for food model covering the data period 1963±1993 revealed that the estimated income and price elasticities remained very similar in value, thus yielding much the same estimate of e. 6 By way of comparison the studies of Kula (1984) for the United States and Sharma et al (1991) for India yielded the following absolute values of e: 1.89 and 1.40 respectively. In both cases TSM demand for food models were employed to obtain estimates of e, although as Jones (1993) points out the Sharma study has a number of shortcomings; for example, the confusion of compensated and uncompensated price elasticities means that the derived e value for India must be incorrect.…”
Section: V E S T I M a T E S O F T H E S O C I A L D I S C O U N mentioning
confidence: 82%
See 2 more Smart Citations
“…From the plausible and statistically valid income and compensated price elasticity estimates of the demand for food, an estimated e value of ¡ 1:60 was derived (see previous section for full details on this). In fact, further estimation of this same demand for food model covering the data period 1963±1993 revealed that the estimated income and price elasticities remained very similar in value, thus yielding much the same estimate of e. 6 By way of comparison the studies of Kula (1984) for the United States and Sharma et al (1991) for India yielded the following absolute values of e: 1.89 and 1.40 respectively. In both cases TSM demand for food models were employed to obtain estimates of e, although as Jones (1993) points out the Sharma study has a number of shortcomings; for example, the confusion of compensated and uncompensated price elasticities means that the derived e value for India must be incorrect.…”
Section: V E S T I M a T E S O F T H E S O C I A L D I S C O U N mentioning
confidence: 82%
“…Longterm social projects are the primary concern in this paper and the Social Time Preference Rate (STPR) is the discount rate measure to be calculated for the UK. 1 There have been several studies, based on the STPR approach, aiming to derive di erent countries' social discount rates: see, for example, Kula (1984Kula ( , 1985 and Sharma et al (1991). Essentially, these studies employ the same approach, an approach taken here but with some empirical re®nement involving the use of cointegration applied to upto-date data.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For an empirical estimation of the marginal utility of money for different income groups in India see e.g.,Sharma, McGregor, and Blyth (1991). It gives intuitive interpretations easily tested in empirical analysis, but is definitely a simplification.…”
mentioning
confidence: 99%
“…These subsistenceoriented and labour-intensive land-use projects aim to provide basic consumption needs (such as staple foods, fuelwood, fodder, small timber for construction and agricultural implements) and employment, the latter to generate some income with which to raise the living standards of the poor (Sharma et al, 1991).…”
mentioning
confidence: 99%